Resistance index of the anterior cerebral artery in the very premature - Ortiz Borda, Elia Maria (2021)
Introduction. The anterior cerebral artery (ACA) resistance index (IR) is used to assess blood flow and is used to determine fetal well-being. Objective. To determine the flow of the anterior cerebral artery in very preterm infants during the first 72 hours of life. Methods. Medical records of very preterm infants treated in the Neonatal Intensive Care Unit of Edgardo Rebagliati Martins National Hospital (HNERM), EsSalud, Lima-Peru, between the years 2011-2019 were reviewed. Results. 56 medical records were reviewed that reported the index of resistance of the anterior cerebral artery in very premature infants of the HNERM. The mean values of the IR of the ACA were: 0,695 at 24 hours; 0,69 at 48 hours; and 0,667 at 72 hours. The mean systolic flow of the cerebral artery prior to 48 hours of life was similar to that of intrauterine life; at 72 hours, the mean diastolic flow was lower. Conclusions. In very preterm infants treated in the Neonatal Intensive Care Unit of the HNHRM, the average RI values of the ACA were: 0,695 at 24 hours; 0,69 at 48 hours; and 0,667 at 72 hours.